Optimization of p-GaN/InGaN/n-GaN Double Heterojunction p-i-n Solar Cell for High Efficiency: Simulation Approach - Aniruddha Singh Kushwaha; Pramila Mahala; Chenna Dhanavantri (International Journal of Photoenergy)
We have conducted numerical simulation of p-GaN/In0.12Ga0.88N/n-GaN, p-i-n double heterojunction solar cell. The doping density, individual layer thickness, and contact pattern of the device are investigated under solar irradiance of AM1.5 for optimized performance of solar cell. The optimized solar cell characteristic parameters for cell area of 1  × 1 mm2 are open circuit voltage of 2.26 V, short circuit current density of 3.31 mA/cm2, fill factor of 84.6%, and efficiency of 6.43% with interdigitated grid pattern.